ADSORPTION OF METHYLENE BLUE FROM AQUEOUS SOLUTION USING FREE AND IMMOBILIZED ALGAE CELLS - Raghad N. M; Abeer I. A (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2023)
This study was aimed to investigate the potential adsorptive behavior of mixed algae for decolorization of methylene blue dye from aqueous solution in the form of free and immobilized. Effects of initial pH value (3-9), biosorbent dosage (0.02-0.5)g/L, and initial concentration (10-50) mg/L for different contact time (0-180) min at 200 rpm shaking speed were investigated. In addition, experimental data were analyzed using adsorption (Langmuir and Freundlich) isotherms as well as kinetic models. The results demonstrated that the maximum decolorization percentage was 93% and 91% by free and immobilized algae, respectively for pH 6, 10 initial concentration, 0.3g/100mL algae dosage, and 90 min contact time. The results revealed that the Langmuir isotherm model was adequate for describing the dye removal process (R2= 0.99) for both forms. Results of pseudo-second order kinetic model revealed best fitting with the sorption data indicating that chemisorption process is the dominant mechanism controlling the dye removal. Furthermore, the characterization study performed using FT-IR and scanning electron micrograph techniques, revealed that the used algal biomass has good biosorption capabilities associated to active groups and surface structure and confirming that the immobilization was successful.